The Influence of Regional Taxes and Levies on Coffee Shops on Medan City Regional Original Income According to an Islamic Economic Perspective - Bin Ziyad Sitanggang, Thariq; Ikhsan Harahap, Muhammad; Lathief Ilhamy Nasution, Muhammad (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
The decrease of local revenue on retribution and restaurant taxes in Medan during the year of 2020 has become interesting to be researched. It then slowly increased back in 2021. A significant raise of revenue also happened to the local retribution and restaurant taxes in 2022. However this was not followed by the local retribution that faced a decline back in 2022. The research aims at observing points to be analyzed and it is found that there are effects on retributions and taxes of coffee shops to the local revenue of Medan from the perspective of Islamic economy. The method of the research applies secondary data obtained from the Central Bureau of Statistics of Medan for five years, beginning in 2019 until 2023. The data information taken from the questions is collected using eviews 10 program. The result of the research indicates that the area of coffee shops has positive and critical influence to the local revenue of Medan. The territorial demands on the coffee shops have positive impacts to unique wages in the area of Medan city. Territorial demands and retributions on the coffee shops also have critical and positive effects to the local revenue of the city of Medan. In terms of Islamic finance system local demands and income are interesting factors that attract individual commitments and become the reasons for a prosperity full of blessings and mercy from Allah SWT.